General and specific combining ability in Serrasalmidae. (9th December 2018) - Costa, Adriano Carvalho; Botelho, Hortência Aparecida; Gomes, Richardson Cesar da Silva; de Sousa Campos, Sergio Augusto; Reis Neto, Rafael Vilhena; Balestre, Marcio; do Prado, Fernanda Dotti; Hashimoto, Diogo Teruo; Martins, Diego Galetti; Porto‐Foresti, Fábio; Lima, Mário; de Freitas, Rilke Tadeu Fonseca
Abstract: This work was carried out to predict the combining abilities, both general and specific, for performance traits and bodily yields of Serrasalmidae. Ninety‐six 30‐day‐old juveniles were purchased from two commercial fish farms, 12 of each of the following eight genetic groups: pacu, pirapitinga, tambaqui, tambacu, tambatinga, patinga, paqui and piraqui. Six fish from each genetic group were grown in 500‐L fibreglass tanks (two tanks per genetic group) until they were 495 days old. At the end of the growth period fish were weighed, subjected to morphometric analysis and processed to obtain their bodily yields. Two nuclear markers and one mitochondrial marker were used to confirm the identity of the animals. Combining abilities were obtained using the method proposed by Griffing in 1956 ( Australian Journal of Biological Science, 4, 463–493) adapted to a mixed models analysis, environmental effects were estimated by the empirical best linear unbiased estimator method and genetic effects (general and specific combining abilities) were estimated with the empirical best linear unbiased predictor. Predictions of the combining abilities of advanced hybrids were obtained by the mixed models mixture method with normal distributions. Tambaqui showed higher general and specific combining abilities than the other groups for most of the variables, making it the most important genetic group. General combining ability makes a greater contribution to phenotypic variance than specific combining ability for most variables, indicating a predominance of genes with an additive effect in the control of evaluated traits.